Psychometric Properties and Convergent Validity of the Shirom–Melamed Burnout Measure in Two German-Speaking Samples of Adult Workers and Police Officers - Schilling, René; Colledge, Flora; Brand, Serge; Ludyga, Sebastian; Gerber, Markus (Frontiers in Psychiatry, 2019)
Burnout is considered an occupation-related psychological syndrome consisting of emotional, physical and cognitive exhaustion. To assess dimensions of burnout, the Shirom-Melamed Burnout Measure (SMBM) is widely used, but its validity and reliability have rarely been examined in adult samples. The aim of this study is to examine the psychometric properties of the German version of the SMBM in two independent samples of adults. In total, 311 adult workers and 201 police officers completed the SMBM, and questionnaires related to perceived stress and mental wellbeing. Descriptive statistics, internal consistency, convergent validity, and factorial validity were assessed for both samples, separately for males and females. The German SMBM had adequate psychometric properties and sufficient convergent validity. In confirmatory factor analyses, we found a good fit for both the first- and second-order model. Furthermore, measurement invariance across gender was observed in both samples. Although the SMBM is a popular instrument among burnout researchers, this study demonstrates for the first time that the SMBM can be considered a valid and reliable tool to assess burnout symptoms in both male and female adults, and across different professional groups. Further, with its 14 items, the SMBM is a succinct and economic self-assessment tool for symptoms of burnout.